Hubungan Antara Harga Diri Dengan Perilaku Konsumtif Pada Mahasiswi - Amalia, Nena, Achmad Dwityanto, S.Psi, M.Si (2016)
Adults can not be denied that each individual has a wide range of needs that must be met. But sometimes an individual actually buy an item that individuals do not need but just to get self-satisfaction, it becomes a trigger consumer behavior. One factor is the self-esteem of the consumer behavior. This study aims: 1) to determine the relationship between self-esteem with the consumer behavior on the students. 2) to determine the level of self-esteem in the student. 3) to determine the level of consumer behavior on the students. 4) to determine the effective contribution of the dignity of consumer behavior on the students. This study population is a student at the Faculty of Psychology UMS from the force in 2013, 2014 and 2015 amounted to 524 people. The sample in this study female college students aged 18-21 years amounted to 100 people. The sampling technique used is incidental sampling. The results of this study can be summarized as follows: 1) there is a negative correlation very significant between self-esteem with the consumer behavior on the students. 2) the level of self-esteem is high. 3) the level of consumer behavior is low. 4) the effective contribution of the dignity of consumer behavior on the students by 6.1%. This means that 93.9% are other factors that influence consumer behavior such as motivation, self-concept, and lifestyle.